(untitled) (Psychology Travelogs, 2023)
The article is devoted to the psychological aspects of reducing the anxiety of servicemen before their deployment to the combat zone. It is noted that anxiety is based on the reaction of fear, and fear, in turn, is an innate reaction to certain situations related to the preservation of the integrity of the organism. The main reason for the anxiety of military personnel is the expectation of unpleasant events in the future, the perception of potential danger, which gradually undermines psychological stability and manifests itself through subjective feelings (discomfort, anxiety, depression, reduced ability to act, etc.), physiological changes (increased heart rate, increased systolic blood pressure, accelerated breathing and metabolism, increased sweating, etc.), change in behavior (increased excitement, nervous movements, tremors of fingers and body, avoidance of social communication, insomnia, aggression, difficulty concentrating, etc.). The emergence of anxiety and its realization occurs as a result of a complex interaction of cognitive, affective and behavioral reactions provoked when a person is affected by various stressful situations. Conducting the research made it possible to understand the correlations between the scales, as well as learn what you need to pay attention to when working with personnel. With the help of the research, the level of situational and personal anxiety among servicemen before sending them to the combat zone was determined. In the future, the conducted research should help to draw up an effective psychocorrective program, which will be aimed at reducing the level of anxiety before participating in combat operations.